PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN GAME KAHOOT TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA SMP - Ni Made Serma Wati; Ni Wayan Dian Permana Dewi (LP3M Universitas PGRI Mahadewa Indonesia, 2024)
This research aims to determine the effect of using the Kahoot game learning media on the motivation and learning outcomes of junior high school students. This research is a type of Quasi-Experimental (semi-experimental) research because in reality this research cannot fully control external variables that influence the implementation of the experiment. The research design used was nonequivalent control group design. The population and sample of this research were 30 teachers at SMP Negeri 1 Kerambitan and 24 people at SMP Negeri 3 Tabanan. At SMP Negeri 1 Kerambitan the number of students in the experimental class was 27 people and the control class was 29 people. Meanwhile, the number of students at SMP Negeri 3 Tabanan in the experimental class was 25 people and the control class was 27 people. Based on the research, the results showed that the average score of students' learning motivation in the experimental class (40.12) was higher than that in the control class (37 .08). The t test results show a t value of 3.320 with a p-value of 0.002, which shows that the difference in learning motivation between the experimental and control classes is statistically significant (p-value < 0.05). Meanwhile, the average value of student learning outcomes in the experimental class (83.10) was also higher than the control class (80.13). The t test results show a t value of 3.135 with a p-value of 0.002, which shows that the difference in cognitive learning outcomes between the experimental and control classes is statistically significant (p-value < 0.05). So it can be concluded that the influence of using the Kahoot game learning media has a positive effect on increasing learning motivation and learning outcomes for junior high school students.